Pengaruh Problem Based Learning dengan Pendekatan Whole Word Method Terhadap Keterampilan Membaca Permulaan Siswa Kelas 1 Sekolah Dasar - Mulyani, Sri; Purwanti, Kartika Yuni (Universitas PGRI Semarang, 2024)
The purpose of this research is (1) To determine the difference in students' beginning reading skills through the Problem-based learning model with the Whole word method approach of grade I elementary school students. (2) To determine the effect of the Problem-based learning model with the Whole word method approach on the beginning reading skills of grade I elementary school students. The population was all first grade students of SD Kristen Bandarjo and SD Wujud Kasih Ungaran. Sampling in research using Non Probability Sampling technique. The results of the research 1) There is a difference in students' beginning reading skills through the problem-based learning model with the whole word method approach to grade I elementary school students. evidenced in the form of the results of the Independent Sample T-Test Test with the level of value obtained significance less than 0.05, namely 0.035 <0.05. So that there is a significant difference between the learning groups. So that there is a significant difference between the experimental and control class study groups, where the average value for the experimental class is 91.15 greater than the control class average of 85.55. 2) There is an effect of using problem-based learning with the whole word method approach as evidenced by the results of the simple Linear Regression Test with a significance value of less than 0.05, namely 0.035 <0.05. So that on the variable of beginning reading skills it is concluded that there is an effect of problem-based learning with the whole word method approach because the mean of the intervention variable is higher by 14.08.